2000
DOI: 10.2214/ajr.174.4.1741093
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Knee at 0.2 and 1.5 T

Abstract: The level of diagnostic accuracy in anterior cruciate ligament tears and meniscus tears is comparable for low- and high-field-strength MR imagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 18 publications
2
38
0
4
Order By: Relevance
“…We were concerned that the use of 0.5-T MRI machines may cause lower results than high-field machines, but it was confirmed by previous studies that the level of diagnostic accuracy in ACL and meniscal tears is comparable for low-and high-field-strength MRI [5].…”
Section: Discussionmentioning
confidence: 96%
“…We were concerned that the use of 0.5-T MRI machines may cause lower results than high-field machines, but it was confirmed by previous studies that the level of diagnostic accuracy in ACL and meniscal tears is comparable for low-and high-field-strength MRI [5].…”
Section: Discussionmentioning
confidence: 96%
“…The use of low-field open configuration magnets in musculoskeletal applications is currently increasing, assuming equivalent accuracy compared with conventional high-field scanners, increased patient comfort, and higher cost effectiveness [1][2][3]13]. Low-field magnets have traditionally been associated with several drawbacks, including long acquisition times, poor signal-to-noise ratio, poor spatial resolution, and the inability to use frequency selective fat saturation [2,3,12].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that low-field devices, especially modern ones, allow for obtaining images of a quality equivalent to the images of high-field resonance (Parizel et al 1995, Baird et al 1998b, Cotten et al 2000, Konar and Lang 2011. However, direct extrapolation of the results obtained with high-field to low-field MRI is not recommended (Baird et al 1999).…”
Section: Resultsmentioning
confidence: 99%